Aspek Hukum Pemberian Insentif Perpajakan bagi Investor di Kawasan Ekonomi Khusus: Studi di Provinsi Sulawesi Utara - Joke Punuhsingon; Rinny Ante; Jocefina Adelleyda Tendean (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the legal aspects of tax incentive policies for investors in the Special Economic Zone (SEZ) of North Sulawesi, Indonesia. Using a normative juridical approach combined with qualitative analysis, the research examines the harmonization of tax regulations between the central and local governments, the effectiveness of legal supervision in implementing tax incentives, and the legal implications of non-compliance with tax incentive regulations. The findings indicate that the implementation of tax incentives in the North Sulawesi SEZ has shown significant growth. Still, challenges remain in terms of regulatory harmonization, institutional capacity, and coordination among stakeholders. The analysis based on Fiscal Law Theory, Legal Certainty Theory, and Distributive Justice Theory highlights the importance of harmonizing regulations, simplifying administrative procedures, and strengthening institutional capacity to ensure the effectiveness and equity of the tax incentive policy. The study recommends strategic measures to enhance the performance of tax incentives in the North Sulawesi SEZ, including strengthening the regulatory aspect, developing institutional capacity, and optimizing coordination and supervision. These recommendations aim to contribute to the more effective and sustainable implementation of tax incentives to promote regional economic growth.